Legal regulation and liability for online fraud based on the use of deepfake technologies and social engineering: foreign experience and directions for its adoption - Saktaganova, A.B.; Saktaganova, I.S. (Bulletin of the Karaganda University “Law Series”, 2026)
In the context of the rapid development of digital technologies, online fraud based on the use of deepfake technologies and social engineering methods poses a significant threat to public safety. The aim of this study is to analyse the legal regulation and liability measures for such crimes in foreign countries, as well as to identify areas where positive international experience can be used to improve national legislation. The study employs general scientific and special methods of cognition, including analysis, synthesis, induction and deduction, as well as formal-legal, comparative-legal and systemic-structural methods. The work examines normative legal acts, judicial practice and doctrinal approaches in a number of foreign countries, including the European Union, the United States and Asian countries, regulating liability for digital forms of fraud. As a result, the main models of legal response to crimes involving deepfakes and social engineering were identified, and their strengths and weaknesses were established. The study concludes that a comprehensive approach to legal regulation is necessary, including clarifying the elements of offences, strengthening preventive measures, and developing international cooperation. The results obtained can be used to formulate pro posals for improving criminal and information legislation.